2022
DOI: 10.3389/fcimb.2022.924725
|View full text |Cite
|
Sign up to set email alerts
|

Oral SARS-CoV-2 Inoculation Causes Nasal Viral Infection Leading to Olfactory Bulb Infection: An Experimental Study

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections can cause long-lasting anosmia, but the impact of SARS-CoV-2 infection, which can spread to the nasal cavity via the oral route, on the olfactory receptor neuron (ORN) lineage and olfactory bulb (OB) remains undetermined. Using Syrian hamsters, we explored whether oral SARS-CoV-2 inoculation can lead to nasal viral infection, examined how SARS-CoV-2 affects the ORN lineage by site, and investigated whether SARS-CoV-2 infection can spread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
3
8
3
Order By: Relevance
“…However, the impact of SARS-CoV-2 on each ORN lineage cell has not been sufficiently verified. We previously reported that all ORN lineage cells are impaired by SARS-CoV-2 (19), and in this study, we verified related longitudinal effects for the first time to our knowledge.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, the impact of SARS-CoV-2 on each ORN lineage cell has not been sufficiently verified. We previously reported that all ORN lineage cells are impaired by SARS-CoV-2 (19), and in this study, we verified related longitudinal effects for the first time to our knowledge.…”
Section: Discussionsupporting
confidence: 85%
“…SARS-CoV-2 infected animal models were prepared following previously reported methods (19, 24). In short, the SARS-CoV-2 strain (JPN/TY/WK-521, provided by the National Institute of Infectious Diseases, Japan) was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations